Evaluation of the accuracy of mammography, ultrasound and magnetic resonance imaging in suspect breast lesions (Clinics, 2020)
OBJECTIVES: In breast cancer diagnosis, mammography (MMG), ultrasonography (USG) and magnetic resonance imaging (MRI) are the imaging methods most used. There is a scarcity of comparative studies that evaluate the accuracy of these methods in the diagnosis of breast cancer. METHODS: A cross-sectional study was carried out through the review of electronic medical records of 32 female patients who underwent breast imaging examinations at a imaging diagnostic center in Teresina, State of Piauı´, Brazil. Patients who had these three imaging methods at the time of the evaluation of the same nodule were included. The nodule must have been classified as suspect by the BI-RADSs system in at least one of the methods. Data from each method were compared with the histopathological examination. Statistical analysis used the calculation of proportions in Excel 2010. RESULTS: MMG showed 56.2%, 87.5%, 81.8%, 66.7% and 71.8% of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy, respectively. USG had 75%, 18.8%, 48%, 42.8% and 46.9% of sensitivity, specificity, PPV, NPV and accuracy, respectively. In turn, MRI had 100%, 50%, 66.7%, 100% and 75% of sensitivity, specificity, PPV, NPV and accuracy, respectively. CONCLUSION: Thus, MRI and MMG were more accurate in evaluating suspicious breast lumps. MRI had a low specificity, mainly to high breast density, while MMG had also sensitivity limited due to high breast density and USG has been proven to be useful in these patients.